Primary Oral Myiasis of Anterior Maxilla in An Intellectually Disabled Female – A Case Report - M, Sridhar; Charantimath, Shivayogi; Bagewadi, Anjana; Kumar S, Lokesh; Panwar, Arun; T, Jayapriya; Keluskar, Vaishali (Journal of Dentistry Indonesia, 2022)
“Myiasis” is a term used to represent invasion caused by fly larvae that affect organs and tissues of human beings and feeds on the host tissue. It is a rare and non-specific pathology that varies according to the species of fly larvae and the area of the body involved. Various factors like extraction wounds, uncontrolled diabetes, necrotic tissues, alcohol addiction, poor oral hygiene, immunocompromised conditions and people with special care needs like debilitated or mentally challenged individuals predispose to develop myiasis. We hereby report a case of oral myiasis of the maxillary anterior region of the palate and labial mucosa, in a 16-year-old female patient with special care needs who for her daily activities is dependent. The diagnosis was confirmed by the presence of pulsating larvae in the lesion and was managed by conservative suffocation therapy involving the turpentine oil topical application followed by the mechanical removal of larvae along with surgical debridement and post-operative antibiotics.